A Conservation Assessment of Historical Mosques: The Case of Sulaimaniyah, Iraqi Kurdistan - wahab ahmed, Hardi; Abdulrahim Abdalla, Barham; Hasan Sleman, Sarko (The Scientific Journal of Cihan University– Sulaimaniya, 2024)
The urgency for meticulous preservation has escalated in light of the invaluable cultural and historical narratives embedded within ancient architectural structures. The article employs a multidisciplinary methodology that combines architectural, historical, and structural analyses in line with the guidelines set forth by the Venice Charter of ICOMOS. Historical area in Sulaimaniyah city is facing a demolishing process which can cause a problem in losing its identity. The research aims at comparing the conservation of the Grand Mosque and Khanaqa Mosque in Sulaimaniyah, Iraq, and comparing it to the neighboring country’s mosque conservation. Our findings reveal that both mosques in Sulaimaniyah face many conservation challenges ranging from material degradation to unauthorized restoration activities. Contrary to our initial hypothesis, the mosques' conservation strategies were incongruous with the Venice Charter's principles, reflecting a wider discrepancy in heritage management in Iraq. We propose targeted conservation measures to address these issues, such as adopting digital documentation technologies, controlled environmental settings, and community-led conservation initiatives. This paper contributes not only to the heritage management discourse in Iraq but also offers insights into the broader discussion concerning the effective preservation of historic religious edifices.